Analisis Perubahan Vegetasi dengan Data Sentinel-2 menggunakan Google Earth Engine - Julianto, Fandi Dwi; Dwi Putri, Dinda Pratiwi; Safi’i, Hafizh Humam (Masyarakat Ahli Penginderaan Jauh Indonesia (MAPIN) /Indonesian Society of Remote Sensing (ISRS), 2020)
Analysis of Vegetation Change Using Sentinel-2 Data in Google Earth Engine (A Case Study of Yogyakarta Special Region Province The Special Region of Yogyakarta (DIY) has a rapid rate of change in vegetation land cover in line with an increase in population that can have an impact on the environment and ecosystem. Remote sensing is a useful technology in determining land cover. The technique can monitor changes in vegetation land regularly from time to time and with various scales. This study aims to determine the changes in vegetation in the Province of DIY with the vegetation index transformation method using the NVDI (Normalized Difference Vegetation Index) algorithm. Processing using Google Earth Engine, which is a cloud-based platform that makes it easy to monitor changes in vegetation quickly and accurately from year to year. The satellite imagery used was a medium resolution satellite image sentinel-2 level 2A and level 1C, which was corrected by atmospheric using SIAC algorithm. Processing results show an average decrease in NDVI values ​​from 2017-2020, with the highest average value in 2018 was 0.73, and the lowest in 2019 was 0.59. Vegetation change was dominated by dense vegetation class, which area turned into medium vegetation class.